THE EFFECT OF PARAMETER AND MATERIAL SETTING VARIATIONS ON PRODUCT QUALITY ON INJECTION MOULDING MACHINES - Muhammad Ikhwan; Diana Yuliastuti (Politek ATK Yogyakarta Press, 2024)
Injection Molding is one of the production processes that is widely used to produce various plastic products. As with other fabrication methods, plastic products produced through the Injection Molding process have the potential to have product defects (defects). This research was carried out to improve the quality of the products produced. The research was conducted in four experiments using HDPE Recycle, HDPE Original, PP and ABS plastic materials with different parameter settings. The parameter settings used include temperature, Injection Speed, Injection Pressure, Holding Speed, Holding Pressure, Rotation Speed, Back Pressure, Plastification Speed, Plastification Pressure, Plastification Potition. In the first experiment using HDPE Recycle material, data was obtained in the form of product defects in Short Shot, Flow Mark, Sink Mark, Warpage. In the second experiment, using Original HDPE material which has better quality than HDPE Recycle because its purity is still maintained, data in the form of defects in Warpage products was obtained. In the third experiment using PP material, Flow Mark and Warpage defects were found in the resulting product. In the fourth experiment using ABS material, defects in Short Shot and Flow Mark were found. From this study, it is known that each material has different properties and qualities so that the setting of injection machine parameters must be adjusted to the material used. From the parameters used in each of these experiments, product defects that arise are also known so that the right solution can be found to overcome the product defect.